Determinants of Exchange Rates And Inflation to Stock Prices in Companies Listed LQ45 Indices on Indonesia Stock Exchange - M. Agustiswan Saputra; Vikka Putri (Politeknik Negeri Madiun, 2023)
This study aims to determine the effect of Exchange Rate and Inflation on Stock Price. The population in this study is Go-Public companies from the LQ45 Index listed on the Indonesia Stock Exchange during the period 2017-2019. The sample selection technique in this study is purposive sampling. Thirty-six companies have been acquired that meet the criteria of the research sample. The results showed that Exchange Rate and Inflation partially or simultaneously did not have a significant effect on the dependent variable, namely the Stock Price of LQ45 Index Companies Listed on the Indonesia Stock Exchange for the 2017-2019 period.